THE CHEMICAL COMPOSITION AND POLLUANTS CONTENT OF SOME ECOLOGICAL AND CONVENTIONAL GREEN FORAGE SOURCES FOR DAIRY COW FEED - Gherasim NACU; Mircea POP; Daniel SIMEANU; Cristina RADU-RUSU; Roxana ZAHARIA; Vasile VINTILǍ (Journal of Applied Life Sciences and Environment)
The quality of feed is very important in dairy milk production. The aim of the current paper was a comparative characterisation in terms of crude chemical composition, Ca and P, heavy metals (Pb, Cd, Zn, Cu), nitrates, nitrites and pesticides, for the natural meadow and green alfalfa, cultivated in ecological and conventional systems, utilised for feeding dairy cows. Sampling and analysis were performed according to established standards and working methods: drying for dry matter (DM); calcination for crude ash (C Ash); Kjeldahl method for crude protein (CP); Soxhlet method for crude fat or ether extract (EE), spectrophotometry for P, nitrates and nitrites; atomic absorption spectrometry for Ca, Pb, Cd, Cu and Zn; gas-chromatography for pesticides. For alfalfa, the highest values in the ecological system were for C Ash (12.68%), EE (2.50%), NFE (35.78%) and Ca (1.79%). For the natural meadow, the highest values in the ecological system were for DM (25.72%), OS (89.32%), EE (2.76%), NFE (45.27%) and Ca (0.70%). The toxic heavy metal content was below the limits allowed (1 mg/kg Cd and 30 mg/kg Pb). For Pb, the values determined from the two feeds were between 0.06 mg/kg and 0.16 mg/kg and for Cd between 0.007 mg/kg and 0.02 mg/kg. The pesticides residuum was under the detection limit of 0.05 mg/kg DM for organo-chlorinated pesticides and 0.001 mg/kg for organo-phosphoric pesticides. All the studied forages were safe regarding pollutants (heavy metals, nitrites, nitrates and pesticides), but statistical differences existed between the production systems, such that the ecological system seems to be better.